PENGURUSAN HARTA WARISAN ANAK DI BAWAH UMUR YANG BERADA DI BAWAH PERWALIAN (STUDI PENETAPAN PENGADILAN AGAMA MEDAN NOMOR 4 PDT.P/2015/PA. MDN) - WINDHA AULIANA YUSRA (PREMISE LAW JURNAL, 2016)
DOSEN PEMBIMBING:1. Hasballah Thaib 2. Muhd Yamin 3. T. Keizerina Devi A Basically the guardianship authority is given to a person to represent the child's immature in performing legal actions in the interest of the child and kindness, which includes custody against myself also treasure his wealth. At its core is the guardianship supervision over people as set in the act, and the management of goods from immature children. Placement of caregivers is very important, especially on the issue of succession. If the child's parents who are immature died then the child will get the treasure inherited from his master's people were then the child must be represented by his guardian, so by consequence the treasure relics obtained a child over the events of his legacy is his parents can meet the sense of fairness and legal certainty. With regard to custody, including therein the guardian appointed or designated by the judge through the determination of the court. Keywords: Management, Inheritance, Child Custody